2018
DOI: 10.1186/s12879-018-3505-y
|View full text |Cite
|
Sign up to set email alerts
|

ATP bioluminescence assay for evaluating cleaning practices in operating theatres: applicability and limitations

Abstract: BackgroundEnvironmental cleaning practice plays an important role in reducing microbial contamination in hospital surfaces and contributes to prevent Healthcare Associated Infections. Adenosine Triphosphate (ATP) bioluminescence assay is a commonly used method for assessing environmental cleanliness on healthcare surfaces. This study tested the feasibility of using ATP-bioluminescence assay for evaluating the efficiency of cleaning procedures in the operating theatre settings, comparing the ATP-bioluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…The traditionally applied methods, to assess microbial air contamination and cleanliness on surfaces in hospital are based on microbiological cultural technology, including active, passive and surfaces sampling [27]. In recent decade, adenosine triphosphate (ATP) bioluminescence assay, which was used to assess environmental surface cleanliness has been proposed [28]. Previous studies have shown that the number of microorganisms that can be cultured only accounts for < 5% of the total microorganisms in air [2931].…”
Section: Introductionmentioning
confidence: 99%
“…The traditionally applied methods, to assess microbial air contamination and cleanliness on surfaces in hospital are based on microbiological cultural technology, including active, passive and surfaces sampling [27]. In recent decade, adenosine triphosphate (ATP) bioluminescence assay, which was used to assess environmental surface cleanliness has been proposed [28]. Previous studies have shown that the number of microorganisms that can be cultured only accounts for < 5% of the total microorganisms in air [2931].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the ATP quantified prior to the sanitisation process did not correlate with the cell counts observed. The quantification of ATP is an indicator of organic material and is not exclusive to microbial contamination, and whilst studies have shown a correlation between ATP levels and total viable counts, a direct relationship remains unclear [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study include bacterial enumeration via CFU/mL, since this method does not account for viable but non-culturable (VBNC) cells [ 71 ]. Finally, although ATP quantification is easy to use and rapid, it is an indicator for organic material and not solely microbial contamination [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bioluminescent sensors of whole cells have benefits over conventional approaches by being faster, more cost effective, easy to carry out and less labor-intensive [198]. While not an alternative to traditional approaches, an ATP-bioluminescence-assay can also be a valuable tool for determining the efficacy of environmental cleanliness procedures even with very low microbial counts [199]. Moreover, bioluminescent techniques often possess several benefits compared to fluorometric techniques mainly because no wavelength of excitation is required for the representation of light.…”
Section: Advantages and Disadvantages Of Atp Bioluminescencementioning
confidence: 99%